Winner Loser Anomaly in Indonesia - Amelia, Rizki; Wijayanto, Andhi (Management Analysis Journal, 2018)
This research examines the market overreaction on the mining companies listed in Indonesia Stock Exchange from 2013 to 2017. The population in this research are all of the mining companies that list in the Indonesia Stock Exchange. The sample are selected according to the criteria of purposive sampling method. Market overreaction are measured by the abnormal return and indicated with ACAR loser portfolio outperformed of ACAR winner portfolio. The result shows that the ACAR loser portfolio doesn’t outperform of ACAR winner portfolio. The significance value of one sample t-test more than 0,05. This research conclude that the overreaction phenomenon on the mining companies in Indonesia Stock Exchange was not found.